2019
DOI: 10.2147/ott.s195675
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identification of key genes and pathways in Ewing’s sarcoma patients associated with metastasis and poor prognosis</p>

Abstract: Background: Ewing sarcoma (ES) is the second commonest primary malignant bone neoplasm. Metastatic status at diagnosis strongly predicted poor prognosis of Ewing sarcoma patients. Yet little was known about the underlying mechanism of ES metastasis. Purpose: This study intended to identify the relationship between key genes/pathways and metastasis/poor prognosis in Ewing's sarcoma patients by using bioinformatic method. Methods: In this study, multi-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Moreover, different novel treatment strategies are evaluating their efficacy in OS metastatic patients through clinical trials [75], with the aim of finding novel treatment strategies for these patients. In ES, similar studies have resulted in several genes linked to metastasis, such as ROR1 [80], MSH2, MSH6, RPA2, and RFC2 genes from the mismatch repair pathway [81], PPP1R1A [82] and TWIST1 proteins [83], the Cad11 adhesion molecule [84], or ERBB4 via activation of the PI3K-Akt-FAK cascade [85]. Moreover, similar to other cancers, hypoxia has been associated with induction of metastasis in OS and ES via regulation of HIF1α through HIF1α [86] or overexpression of CXCR4 in ES [87], amongst others.…”
Section: The Role Of Exosomes In Bone Sarcoma Metastasismentioning
confidence: 88%
“…Moreover, different novel treatment strategies are evaluating their efficacy in OS metastatic patients through clinical trials [75], with the aim of finding novel treatment strategies for these patients. In ES, similar studies have resulted in several genes linked to metastasis, such as ROR1 [80], MSH2, MSH6, RPA2, and RFC2 genes from the mismatch repair pathway [81], PPP1R1A [82] and TWIST1 proteins [83], the Cad11 adhesion molecule [84], or ERBB4 via activation of the PI3K-Akt-FAK cascade [85]. Moreover, similar to other cancers, hypoxia has been associated with induction of metastasis in OS and ES via regulation of HIF1α through HIF1α [86] or overexpression of CXCR4 in ES [87], amongst others.…”
Section: The Role Of Exosomes In Bone Sarcoma Metastasismentioning
confidence: 88%
“…Moreover, fluctuations in EWS-FLI1 levels are not the only mechanism known to initiate EwS dissemination 51 , and several candidates such as chemokine receptor CXCR4 signalling 52 , chromatin modifiers 53 , cadherins 54 , micro-RNAs 55 and interactions with the tumour microenvironment including glucocorticoids 56,57 have been proposed. In our in vivo proof-of-principle experiments, reduction in onset and number of lung metastases depending on dose and timing of VP treatment did not achieve statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…The findings highlighted the MMR pathway as the most significantly enriched KEGG pathway in EWS patients [73]. The expression levels of key MMR components including MSH2 and MSH6 are found to be significantly associated with metastasis, shorter EFS, and overall poor prognosis in Ewing sarcoma patients [73]. Several studies have investigated the role of MMR pathway in osteosarcoma.…”
Section: Msh2-msh6 (Mutsα)mentioning
confidence: 99%
“…A study conducted by Li et al, emphasized the importance of MMR pathway in Ewing sarcoma and showed that the expression levels of MSH2 and MSH6 is correlated with an increased chance of metastasis and poor prognosis in these patients [73]. They used the GEO database to investigate the correlation of the key dysregulated genes and pathways with prognosis information and metastasis status of the Ewing sarcoma patients [73]. The findings highlighted the MMR pathway as the most significantly enriched KEGG pathway in EWS patients [73].…”
Section: Msh2-msh6 (Mutsα)mentioning
confidence: 99%
See 1 more Smart Citation